ANALISIS STRUKTUR TEKS KAKAWIN NITI SASTRA - I Putu Agus Aryatnaya Giri; Kadek Dwi Sentana Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Among the Balinese, Old Javanese literary works, especially kakawin which is very well known, are still alive and growing. The literary works of kakawin by the Balinese are read, studied and lived out in traditional gatherings which are commonly called mabebasan. Moving on from that reason, it would be very interesting to research Old Javanese literature, one of which is Kakawin Niti Sastra. Research on this kakawin needs to be done because this Kakawin Niti Sastra contains ethical and leadership values which are very important as guidelines in social life. However, on this occasion, it will be focused on the literary work through a study of text structure, as an initial effort in documenting the study of Old Javanese Literature, especially Kakawin Niti Sastra. The results showed that the Kakawin Niti Sastra text structure consisted of a formal structure and a narrative structure. The formal structure consists of: 1) guru-laghu, namely the lightness or length of the syllable sung on a kakawin, 2) the 120 stanza/pada, which is a collection of lines (carik) bound by a single unit of meaning and tone, 3) Language manuscripts, namely Old Javanese and Indonesian, 4) Colophon, namely the writer's notes, generally in manuscripts or publications, containing information about the place, time and the copy of the manuscript. The Niti Sastra manuscript in Indonesian is published by Balai Prestaka. Only then was written by the PGAHN Team 6 Years Singaraja on December 12th, 1971 and officially published in 1983-1984, 5) Alamkara, namely ornaments, decorations, stylistic ornaments, artistic language, convoluted language or too contrived, something stunning or enchanting, fantastic form. The narrative structure in Kakawin Niti Sastra consists of: 1) Manggala, which is the initial or opening part of the writing of Kakawin Niti Sastra's literary works, whose contents are in the form of tribute to Bhatara Hari and Bhatara Surya. 2) The corpus is the content of the entire Kakawin Niti Sastra script, namely the teachings of ethics and leadership, 3) The epilogue is the closing verses in Kakawin Niti Sastra which ends with